Pipeline construction project : a study on the effectiveness of trenchless technology from project management perspective - Syahir Amri, Musa (2014)
Development of technology in pipeline construction industry nowadays brings alternative method that can be used in installing the underground pipeline which able to reduce the cost usage for a project. Open-cut is a common method used in installing underground pipeline but with surface disruption and brings negative impact to communities, trenchless technology may offer viable alternative with innovative method and cost-effectiveness. Therefore, the research aims to compare the cost effectiveness between trenchless technology and open cut method. The research also provides the criteria to be considered in implementing the trenchless technology. Close-ended survey questionnaire has been used as research methodology while scope of study focusing on east coast construction contractors. There are four respondents that involved in the research. The study proved that trenchless technology is the most cost effective compare to the open-cut method. Comparison has been done based on preconstruction and construction (direct and indirect) cost. The research also identified the criteria to be considered in trenchless technology by highlight on the pipe jacking and horizontal directional drilling. Limitation for the research is the small amount of contractors who specialize in trenchless technology. Future research is needed to consider the other cost factors which may contribute to the project cost.